Decision Support System for Asset Management using the Simple Additive Weighting Method - Ni Made Yeni Dwi Rahayu; Ni Putu Dewi Eka Yanti (International Journal of Management Science and Information Technology, 2025)
Effective and efficient asset management is a crucial aspect in supporting the operational sustainability of an organization. However, the decision-making process in determining whether an asset should be retained, repaired, or replaced is often conducted subjectively and lacks structure. This study aims to develop a Decision Support System for asset management using the Simple Additive Weighting method to assist in evaluating assets objectively based on multiple criteria. The developed system includes features such as a master data menu, alternative data input, SAW-based calculation processes, and a recommendation result display. System testing results showed that the values for accuracy, precision, recall, and specificity were each 80%, with 4 True Positive, 4 True Negative, 1 False Positive, and 1 False Negative. Based on these results, the system is considered valid and suitable for use as a decision-making tool in structured and measurable asset management processes. This level of accuracy also reflects the system's ability to accurately identify and classify data under both positive and negative conditions. Therefore, it can be concluded that this decision support system has a good level of reliability and is suitable for use as a supporting tool in asset management decision-making.